Ruins of modernity - Adams, Julia; Hell, Julia; Hell, Julia; Schönle, Andreas; Schönle, Andreas; Steinmetz, George; Steinmetz, George (Politics, History, and Culture : 30, 2010)
Images of ruins may represent the raw realities created by bombs, natural disasters, or factory closings, but the way we see and understand ruins is not raw or unmediated. Rather, looking at ruins, writing about them, and representing them are acts framed by a long tradition. This unique interdisciplinary collection traces discourses about and representations of ruins from a richly contextualized perspective. In the introduction, Julia Hell and Andreas Schönle discuss how European modernity emerged partly through a confrontation with the ruins of the premodern past.Several contributors discuss ideas about ruins developed by philosophers such as Immanuel Kant, Georg Simmel, and Walter Benjamin. One contributor examines how W. G. Sebald's novel The Rings of Saturn betrays the ruins erased or forgotten in the Hegelian philosophy of history. Another analyzes the repressed specter of being bombed out of existence that underpins post-Second World War modernist architecture, especially Le Corbusier's plans for Paris. Still another compares the ways that formerly dominant white populations relate to urban-industrial ruins in Detroit and to colonial ruins in Namibia. Other topics include atomic ruins at a Nevada test site, the connection between the cinema and ruins, the various narratives that have accrued around the Inca ruin of Vilcashuamán, Tolstoy's response in War and Peace to the destruction of Moscow in the fire of 1812, the Nazis' obsession with imperial ruins, and the emergence in Mumbai of a new "kinetic city" on what some might consider the ruins of a modernist city. By focusing on the concept of ruin, this collection sheds new light on modernity and its vast ramifications and complexities.Contributors. Kerstin Barndt, Jon Beasley-Murray, Russell A. Berman, Jonathan Bolton, Svetlana Boym, Amir Eshel, Julia Hell, Daniel Herwitz, Andreas Huyssen, Rahul Mehrotra, Johannes von Moltke, Vladimir Paperny, Helen Petrovsky, Todd Presner, Helmut Puff, Alexander Regier, Eric Rentschler, Lucia Saks, Andreas Schönle, Tatiana Smoliarova, George Steinmetz, Jonathan Veitch, Gustavo Verdesio, Anthony Vidler